PERANCANGAN BUKU BERJUDUL “MY ACNE JOURNEY, KENALI, ATASI, CEGAH JERAWAT” UNTUK REMAJA USIA 13-18 TAHUN DENGAN TEKNIK ILUSTRASI DIGITAL - Angel Beauty; Yana Erlyana (Jurnal Dimensi DKV Seni Rupa dan Desain, 2022)
Book Design entitled “My Acne Journey, Kenali, Atasi, Cegah Jerawat” for Teenagers Age 13-18 with Digital Illustration Techniques. The design of the final project in the form of a journal entitled "My Acne Vulgaris" aims to become an interactive information medium by adapting the bullet journal system. This book contains an introduction to acne vulgaris in general and how to treat acne-prone skin that can be applied to everyday life for teenage girls aged 13-18 years. The research method applied is using a descriptive qualitative method by collecting data from the results of the literature, questionnaires, interviews, internet and observation. Based on the results of data collection, it is known that acne vulgaris can affect mental health and reduce self-confidence, especially in women, so knowledge about acne vulgaris is needed. In designing this book, attention to design rules combined with illustrations can be an attraction. Through this book, it is hoped that it can become an interactive medium to increase knowledge about acne vulgaris and increase self-confidence in adolescents.